Beware of a multi‐fibroid uterus: The importance of ultrasound reporting in the early detection of uterine sarcomas. Issue 4 (November 2016) - Hannemann, Bernard; McKnoulty, Matthew; Kothari, Alka
Abstract: Primary uterine malignancy masquerading as a benign leiomyoma is a rare yet devastating condition if missed on ultrasound. Although there are no current guidelines to aide in early ultrasound identification of these high‐risk patients prior to histological analysis, certain imaging characteristics may heighten the suspicion of malignancy. Unfortunately, these atypical features are often not included in ultrasonographic reports resulting in delayed treatment and catastrophic consequences. We present a case of a uterine Ewing's sarcoma (ES), which was diagnosed as a multi‐fibroid uterus on initial ultrasound. The lack of clinical suspicion resulted in a delay to definitive diagnosis and a sub‐optimal surgical resection. We compare this to a standard case of a multi‐fibroid uterus in order to highlight the differences in ultrasonographic appearance. This case delineates the importance of accurate identification and open reporting of suspicious features in order to assist ultrasonographers and specialist gynaecologists in creating a differential diagnosis of an otherwise common condition. A high index of suspicion of atypical lesions may lead to early life‐saving interventions and careful tissue control during surgery, resulting in improved patient outcomes.